Fundamental roles of the innate-like repertoire of natural antibodies in immune homeostasis - Vas, Jaya; Grönwall, Caroline; Silverman, Gregg (Frontiers in Immunology, 2013)
The composition of the early immune repertoire is biased with prominent expression of spontaneously arising B-cell clones that produce IgM with recurrent and often autoreactive binding specificities. Amongst these naturally-arising antibodies (NAbs) are IgM antibodies that specifically recognize damaged and senescent cells, often via oxidation-associated neo-determinants. These NAbs are present from birth and can be further boosted by apoptotic cell challenge. Recent studies have shown that IgM NAb to apoptotic cells can enhance phagocytic clearance, as well as suppress pro-inflammatory responses induced via Toll-like receptors, and block pathogenic IgG-immune complex (IC)-mediated inflammatory responses. Specific antibody effector functions appear to be involved, as these anti-inflammatory properties are dependent on IgM-mediated recruitment of the early recognition factors of complement. Clinical surveys have suggested that anti-AC IgM NAbs may modulate disease activity in some patients with autoimmune disease. In mechanistic studies, anti-AC NAbs were shown to act in dendritic cells by inhibition of the Mitogen Activated Protein Kinase (MAPK) pathway, a primary signal transduction pathway that controls inflammatory responses. This immunomodulatory pathway has an absolute requirement for the induction of MAPK Phosphatase-1. Taken together, recent studies have elucidated the novel properties of a class of protective NAbs, which may directly blunt inflammatory responses through a primitive pathway for regulation of the innate immune system.